A Schiff base ligand for photoinduced atom transfer radical polymerization. Issue 12 (4th March 2021) - Xu, Xiaoling; Hong, Mei; Bao, Chunyang; Wang, Yan; Chen, Jing; Li, Die; Wang, Tianheng; Zhang, Qiang
Abstract : A claw-type Schiff base, tris[ N -(2-pyridylmethyl)-2-iminoethyl]amine (Py3 Tren), is used as an active ligand for photoinduced atom transfer radical polymerization (Photo-ATRP). Abstract : A claw-type Schiff base, tris[ N -(2-pyridylmethyl)-2-iminoethyl]amine (Py3 Tren), is used as an active ligand for photoinduced atom transfer radical polymerization (Photo-ATRP). CuBr2 /Py3 Tren was employed as a catalyst for Photo-ATRP of methyl methacrylate (MMA) under the irradiation of ultraviolet or visible light. Well-defined poly(MMA) could be synthesized with high chain-end functionality confirmed by in situ chain extension. Temporal control of Photo-ATRP was successfully demonstrated by switching the light on and off. The polymerization mechanism was finally discussed through UV/vis spectroscopy and electrospray ionization mass spectrometry (ESI-MS) experiments.